Analisa Kepuasan Mahasiswa AMIK Mahaputra Riau Terhadap SISFO dengan Metode End User Computing Satisfaction - Annisa Salsabila; Medyantiwi Rahmawita Munzir; Tengku Khairil Ahsyar; Megawati Megawati (JURIKOM (Jurnal Riset Komputer), 2022)
AMIK Mahaputra Riau is one of the universities that implements an academic system called SISFO (Information System). SISFO assists in the management of data related to academics such as, student and lecturer data, recaps of lecture results and lecture schedules. In its application, SISFO still found several problems such as, the absence of a complaint feature for users, the color of the system display that seems monotonous, incomplete information about the total score of the entire semester, the system still inputs incorrect data and the length of time the system updates the data. During the implementation of the system, there has never been any research and assessment of the level of user satisfaction with the quality of the system used. From these problems, an analysis is needed that can measure user understanding of the system used, and is expected to provide input to related parties which can later be used to develop and improve the quality of the academic system and help AMIK Mahaputra Riau to reduce risks that will later occur. The method used in this study is the End User Computing Satisfaction (EUCS) method. This study used 72 respondents who were determined using the Quota Sampling technique.  Data processing is carried out using SmartPLS software version 3.2.  In this study, it was found that 57.6% of students were quite satisfied with SISFO